Suspension of Inheritance Distribution: A Review of Islamic Law and Its Implications - Siregar, Nurma Harana Mora; Dasopang, Nur Sania (El-Sirry: Jurnal Hukum Islam dan Sosial, 2025)
This research examines the suspension of the distribution of inheritance from the perspective of Islamic law and its implications for the justice and benefit of the heirs. The focus of the research is directed at the normative analysis of the normative basis of inheritance division in fiqh mawaris, the limitations of deferral ability, and the social and cultural factors behind the practice of postponing the distribution of inheritance in Muslim society. This research uses a literature study method with a normative qualitative approach, through an analysis of classical and contemporary Islamic law sources, including the Qur'an, hadith, fiqh books, and modern Islamic legal literature. The results of the study show that in principle, the distribution of inheritance in Islam is recommended to be carried out immediately after the fulfillment of the heir's obligations, such as debt repayment and the execution of a will. However, the suspension of the distribution of inheritance can be justified under Islamic law as long as it is based on the agreement of all heirs, does not cause tyranny, and aims to maintain the common good. The implications of the suspension show that there is a potential for conflict and injustice if it is not accompanied by clarity of rights, so a comprehensive legal understanding is needed so that the practice of suspension remains in line with the principles of justice.